The Limitations of Exfoliative Cytology for the Detection of Epithelial Atypia in Oral Leukoplakias - Dabelsteen, E. (Nature Publishing Group, 1971)
Two hundred and ninety-nine oral leukoplakias were examined by exfoliative cytology; 83 of these lesions were biopsied because of clinical or previous histological features. Epithelial atypia was found in 16 of these biopsies, exfoliative cytology detecting epithelial atypia in only 6 of these cases. Thus exfoliative cytology used alone would have led to a false negative diagnosis in 10 out of 16 (62%) of the cases with epithelial atypia verified by histology. In addition, in no instance was exfoliative cytology responsible for the detection of an epithelial atypia that had been overlooked by consideration of clinical or previous histological features. Exfoliative cytology was successful in the detection of atypia only in those cases in which the surface of the lesion was either ulcerated or not keratinized; all keratinized lesions with atypia yielded negative cytology. The results of this study lead to the conclusion that exfoliative cytology is not to be recommended as a routine diagnostic or screening procedure for the detection of possibly pre-malignant features in oral leukoplakias.